An In‐Situ Neutron Diffraction and DFT Study of Hydrogen Adsorption in a Sodalite‐Type Metal–Organic Framework, Cu‐BTTri. Issue 8 (15th January 2019) - Asgari, Mehrdad; Semino, Rocio; Schouwink, Pascal; Kochetygov, Ilia; Trukhina, Olga; Tarver, Jacob D.; Bulut, Safak; Yang, Shuliang; Brown, Craig M.; Ceriotti, Michele; Queen, Wendy L.
Abstract : Herein we present a detailed study of the hydrogen adsorption properties of Cu‐BTTri, a robust crystalline metal–organic framework containing open metal‐coordination sites. Diffraction techniques, carried out on the activated framework, reveal a structure that is different from what was previously reported. Further, combining standard hydrogen adsorption measurements with in‐situ neutron diffraction techniques provides molecular level insight into the hydrogen adsorption process. The diffraction experiments unveil the location of four D2 adsorption sites in Cu‐BTTri and shed light on the structural features that promote hydrogen adsorption in this material. Density functional theory (DFT), used to predict the location and strength of binding sites, corroborate the experimental findings. By decomposing binding energies in different sites in various energetic contributions, we show that van der Waals interactions play a crucial role, suggesting a possible route to enhancing the binding energy around open metal coordination sites. Abstract : The correct structure of a well‐known metal–organic framework (MOF), Cu‐BTTri, has been defined by means of in‐situ diffraction techniques. The in‐situ neutron diffraction technique, coupled with detailed DFT studies, has led to a deep understanding of the chemical and structural parameters influencing hydrogen adsorption in MOFs.